Uncommon sense - Shapiro, Ian 1956- (Yale University Press, 2024)
A spirited defense of the Enlightenment against assaults from both the left and the right that explains its urgent implications for our contemporary politics Ours is an age when optimism about politics is hard to come by. Ian Shapiro explains why this is so and, without minimizing the daunting challenges, spells out an appropriate response. Written in the indomitable spirit exemplified by Tom Paine, Uncommon Sense is a rich source of insight and inspiration in dark political times. The Enlightenment commitments to reason and science are under assault from the Postmodern Left and the Authoritarian Right. Shapiro explains why the attacks are misguided and politically destructive. He agrees with the critics that there are no universal principles of justice that transcend political battles and no fair, impartial rules to govern the distribution of income, wealth, rights, or opportunities. But abandoning the search for them as futile does not mean junking the Enlightenment's core political goal: to deploy the tools of reason and science to fight domination. Democracy is essential to vindicating that goal, yet citizens in many democracies are profoundly alienated and many democracies are in danger of failing. Shapiro explains what has gone wrong, debunks ill-considered remedies, and spells out better ones-deepening and extending his previous writing on political theory and democratic politics
Keywords: PHILOSOPHY / Political; Democracy; Enlightenment; Aufklärung; Politische Theorie; Demokratie; Politische Philosophie